2022
DOI: 10.1111/jocn.16429
|View full text |Cite
|
Sign up to set email alerts
|

Children living with long‐term conditions and their experiences of partnership in nursing care: An integrative systematic review

Abstract: Aims and Objective:To describe the experiences of nursing care and partnership nursing as expressed by children living with long-term conditions.Background: Children with long-term conditions have higher rates of hospitalisations and adverse events in hospital, yet little is known about their experiences of nursing care. How children perceive partnership in care with their families and nurses is of interest in the achievement of safe and effective care Design: An integrative review following Joanna Briggs Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…This is crucial as children with longterm conditions often face longer hospital admissions and have an increased morbidity and mortality (AIHW, 2022). Often, the level of child and parent involvement changes based on the nurse providing the care on that day, with the nurse utilising subjective data and information to determine how care will be provided and the roles each party will play (Barratt et al, 2021(Barratt et al, , 2022. Previous research has demonstrated that children benefit from having an active role in partnership with their parents and nursing staff (Barratt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is crucial as children with longterm conditions often face longer hospital admissions and have an increased morbidity and mortality (AIHW, 2022). Often, the level of child and parent involvement changes based on the nurse providing the care on that day, with the nurse utilising subjective data and information to determine how care will be provided and the roles each party will play (Barratt et al, 2021(Barratt et al, , 2022. Previous research has demonstrated that children benefit from having an active role in partnership with their parents and nursing staff (Barratt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Often, the level of child and parent involvement changes based on the nurse providing the care on that day, with the nurse utilising subjective data and information to determine how care will be provided and the roles each party will play (Barratt et al, 2021(Barratt et al, , 2022. Previous research has demonstrated that children benefit from having an active role in partnership with their parents and nursing staff (Barratt et al, 2022). Children who have a more active role in their own health care often find their own voice within the partnership as they have been taught the importance of shared decision-making and autonomy from a younger age, which can help empower their self-advocacy for a condition that they may have for their entire life (Barratt et al, 2022;Coyne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While children observed the adults around them collaborating and forming partnerships in terms of asthma care, they reported that they were unable to participate in their own care and were frequently passive observers. If children are not allowed to participate in their own healthcare, they may experience fear, anxiety and prolonged emotional trauma as they try to navigate a complex system of healthcare (Barratt et al, 2022). While existing literature indicates the importance of letting family caregivers retain control over their children's asthma, our study emphasises the importance of giving children a sense of agency and power over their own healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This approach provides opportunities for both parties to participate in decision‐making regarding the child's asthma care, thereby improving family outcomes. If, on the contrary, this partnership is adult‐centric, children may lose their voice to the heavy voices of adults, thus resulting in an imbalance of power that may negatively affect them as they mature and seek more control and knowledge over their own health care (Barratt et al, 2022). Future research should therefore focus on developing policies that promote the active participation of children in their asthma care planning.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%